Perception of Kogi State University Agricultural Students on Farming as a Career - O.J, Saliu; U, Onuche; H, Abubakar (International Journal of Sustainable Agricultural Research, 2017)
This study examined the perception of Kogi State University Agricultural Students on farming as a career. Primary data were collected using structured interview schedule to pick 150 students in the study area. Stratified random sampling technique was used to pick 30 students from each level (100-500). Data collected were analyzed using descriptive statistics such as frequency count, percentage and mean score on a 3 point likert-type of scale. The result of the study indicated that a large percentage (42.7%) of students were from household size of 4 to 6 which is fairly large for the needed labour force for agricultural activities. Many (56%) of the students had no farming experience before their enrolment into the university. The study further showed that most of the students had negative attitude when they resumed in 100 level mean score (X) (2.30) but are now greatly influenced by agricultural education impacted by trained agricultural experts (X) (2.67). Students Industrial Work Experience Scheme (SIWES) programme had also positively changed the students attitude to farming (2.25). Most respondents (X) (2.58) 86% showed willingness to engage in practical agricultural enterprise if supplied with the necessary agricultural inputs. Also willingness to embark on poultry farming had (X) (2.73), fish farming had ms (2.49), cash crop farming had (X) (2.19) and arable crop farming had (X) (2.12) which represented a popular perception among the respondents. Piggery farming with (X) (1.47) and beekeeping with (X) (1.33) had the least indication of interest by the students. Implementation of government agricultural policies that will ensure regular input and attractive market price could motivate agricultural graduates to embrace farming as a career.